Post-COVID symptoms in EU cross-border cooperation - Medeiros, E.; Guillermo-Ramirez, M.; Ocskay, G.; Peyrony, J. (Észak-magyarországi Stratégiai Füzetek, 2022)
The COVID-19 pandemic has changed the conditions of normal life in many aspects. However, it most impacted the life of people around national borders. What is more, while in other regions, after the successful vaccination campaigns, life begins to return normal, the borderlands still display signs of the effect of the pandemic, what we could call post-COVID symptoms. The study points out the symptoms which seem likely to stay with us for a long time and formulates recommendations for treatment.